Visual advisory warnings about hidden dangers: Effects of specific symbols and spatial referencing on necessary and unnecessary warnings. (October 2018) - Schwarz, Felix; Fastenmeier, Wolfgang
Abstract: Augmented reality has the potential to improve the effectiveness of collision warnings in vehicles because they inherently convey spatial information about the hazard and can guide the attention of the driver towards it. For future warning systems, which can detect sight obstructed dangers, related work already revealed some advantages. In a driving simulator study with 80 participants, we investigated the effects of three corresponding design parameters which are commonly integrated at augmented reality warnings. This study analyzes the individual contribution of specific warning symbols, warning animation, and spatial referencing. Part one of the study concentrates on the effectiveness of necessary warnings and part two on the drivers' compliance despite false alarms. Compared to the control condition with static unspecific warning symbols, static specific warning symbols depicting the type and motion direction of the hazard led to several but inconsistent advantages. The scaling animation only improved subjective evaluation. However, spatial referencing of an (unspecific) warning symbol consistently improved drivers' reactions to as well as evaluations of necessary and unnecessary warnings. The results emphasize the potential of spatial referencing, particularly for in-vehicle warnings of future collision avoidance systems. Highlights: Effects of three design parameters of augmented reality warnings are analyzed individually. Symbolic information and zooming animation do not provide consistent benefit. Spatial referencing shows clear benefits for warning effectiveness.